The role of class IIa histone deacetylases in regulating endothelial function - Shen, Zexu; Bei, Yun; Lin, Haoran; Wei, Taofeng; Dai, Yunjian; Hu, Yangmin; Zhang, Chao; Dai, Haibin (Frontiers in Physiology, 2023)
Vascular endothelial cells (ECs) are monolayer cells located in the inner layer of the blood vessel. Endothelial function is crucial in maintaining local and systemic homeostasis and is precisely regulated by sophisticated signaling pathways and epigenetic regulation. Endothelial dysfunctions are the main factors for the pathophysiological process of cardiovascular and cerebrovascular diseases like atherosclerosis, hypertension, and stroke. In these pathologic processes, histone deacetylases (HDACs) involve in epigenetic regulation by removing acetyl groups from lysine residues of histones and regulating downstream gene expression. Among all HDACs, Class IIa HDACs (HDAC4, 5, 7, 9) contain only an N-terminal regulatory domain, exert limited HDAC activity, and present tissue-specific gene regulation. Here, we discuss and summarize the current understanding of this distinct subfamily of HDACs in endothelial cell functions (such as angiogenesis and immune response) with their molecular underpinnings. Furthermore, we also present new thoughts for further investigation of HDAC inhibitors as a potential treatment in several vascular diseases.